ANÁLISE DA GESTÃO DA QUALIDADE DOS SERVIÇOS PRESTADOS NA TESOURARIA DA UNIJUÍ - SOARES, JÚLIO C. V.; SCHWIDERKE, CRISTINA; ZWICK, ELISA; MACHADO, JAMILE D. M.; OLIVEIRA, MARIA S. D.; CUNHA, MARIELI D.; SCHIRMER, ROSELI F. (Salão do Conhecimento, 2013)
Resumo